Malay women readings of Korean drama - Ruslan, Norbaiduri; Abdul Latif, Sakinah (Geist Science, 2016)
Korean drama has a stronghold position in the global entertainment scene. In Malaysia, the craving for Korean drama started about a decade ago when the hit-drama 'Winter Sonata' made its debut. Korean drama become household favorites, especially among women. This study reports some findings on the audience reception study of Korean drama among avid Korean drama fans. Four focus group interviews using semi-structured protocols were conducted of which two groups were comprised of adolescents and another two groups were adults. The main research question was, "How do Malay women read Korean drama media text?" The analysis of the verbatim transcriptions yielded eight salient themes: 1)Male centric; 2) Family-oriented; 3) Female-centric; 4) Cultural values; 5) Storyline; 6)Cosmopolitan lifestyle; 7)Realism (Fantasy Love; 8) Parasocial relationship. The findings are discussed from Stuart Hall's dominant, preferred, negotiated and oppositional readings,